2021
DOI: 10.1002/acm2.13055
|View full text |Cite
|
Sign up to set email alerts
|

An electronic portal image device (EPID)‐based multiplatform rapid daily LINAC QA tool

Abstract: PurposeTo develop an efficient and economic daily quality research tool (DQRT) for daily check of multiplatform linear accelerators (LINACs) with flattening filter (FF) and flattening filter‐free (FFF) photon beams by using an Electronic Portal Image Device (EPID).Materials and MethodsAfter EPID calibration, the monitored parameters were analyzed from a 10 cm × 10 cm open and 60° wedge portal images measured by the EPID with 100 MU exposure. Next, the repeatability of the EPID position accuracy, long‐term stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Se han propuesto diferentes métodos para el CC que utilizan como instrumentos de medida los propios sistemas de imagen del acelerador. 84 Estos dispositivos permiten medir y analizar en poco tiempo los principales parámetros del acelerador. Algunos fabricantes ya han incorporado en sus plataformas métodos propios que controlan los principales parámetros del acelerador con una frecuencia diaria.…”
Section: Perspectivasunclassified
“…Se han propuesto diferentes métodos para el CC que utilizan como instrumentos de medida los propios sistemas de imagen del acelerador. 84 Estos dispositivos permiten medir y analizar en poco tiempo los principales parámetros del acelerador. Algunos fabricantes ya han incorporado en sus plataformas métodos propios que controlan los principales parámetros del acelerador con una frecuencia diaria.…”
Section: Perspectivasunclassified
“…Therefore, it has been widely applied in accelerator quality control, position verification, and dose verification. 1,2 In daily work, it has been observed that under the single isocenter condition, the potential shifts of the EPID may be introduced when executing portal dosimetry (PD) plans for bilateral breast cancer, pleural mesothelioma, and lymphoma. These shifts are relative to the calibration positions of EPID and result in significant discrepancies in the plan verification results.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of volumetric arc therapy (VMAT) techniques and kilovoltage cone beam CT (CBCT), the main function of the megavoltage EPID panel in many departments is for use as a quality assurance (QA) tool. A number of publications describe the use of megavoltage EPID panels for tests such as MLC position calibration, dose‐output constancy, beam flatness/symmetry, radiation field size, and kilovoltage (KV) to megavoltage (MV) isocenter calibration/verification 1‐6 …”
Section: Introductionmentioning
confidence: 99%
“…A number of publications describe the use of megavoltage EPID panels for tests such as MLC position calibration, dose‐output constancy, beam flatness/symmetry, radiation field size, and kilovoltage (KV) to megavoltage (MV) isocenter calibration/verification. 1 , 2 , 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation